Solvent‐Enhanced Conformational Flexibility of Cyclic Tetrapeptides. Issue 13 (2nd July 2019) - Berger, Nadja; Wollny, Laura J. B.; Sokkar, Pandian; Mittal, Sumit; Mieres‐Perez, Joel; Stoll, Raphael; Sander, Wolfram; Sanchez‐Garcia, Elsa
Abstract: The front cover artwork is provided by the groups of Prof. Wolfram Sander (Ruhr‐Universität Bochum) and Prof. Elsa Sanchez‐Garcia (University of Duisburg‐Essen). The image shows the structure of a cyclic tetrapeptide in solution. The dynamics of the peptide in explicit solvent was investigated using several computational and experimental techniques at different temperatures. Read the full text of the Article at 10.1002/cphc.201900345 . Abstract : "Solvent and temperature can affect the structural properties of cyclic peptides by controlling their flexibility. Here, we investigate two cyclic peptides, featuring beta turns…" This and more about the story behind the front cover can be found in the Article at10.1002/cphc.201900345 .